Implementing a Document Archive for the Site of Memory and Human Rights: The Case of the Corporación Parque por la Paz Villa Grimaldi - Iduarte Cofré, María Elena (Revista General de Información y Documentación, 2015)
Chile's recent history remembers the victims of a repressive regime persecuted between 1973 and 1990, systematically executed and disappeared persons. The Corporación Parque por la Paz Villa Grimaldi tries to keep the collective memory of the Chileans living memory of those victims, that through projects of education and dissemination of human rights. One such project was the implementation of a documentary archive on the site of former torture center memory and difficulties involved for the project that that site is Historic Landmark and the results of documentary organization after project implementation.
Keywords: Archive; Chile; Conservation; Human Rights; Memory location.